Becoming African psychologists: Decolonisation within a postgraduate psychology module at the University of Johannesburg - Joosub, N. (South African Journal of Higher Education, 2021)
There is a compelling need for curriculum design and processes of teaching in South African higher education institutions to heed calls for decolonisation and relevance. Within university Psychology teaching spaces, both the what and the how of knowledge production require transformation and epistemic emancipation. This study explored the perceptions of students regarding the decolonisation processes within a postgraduate Psychology module at the University of Johannesburg. Through the thematic analyses of blogs written by students, results indicated the students benefitted from decolonisation initiatives through three interdependent processes. These processes were (1) Learning Real World Skills from Peers, (2) Bringing it Home: Making Psychology Relevant, and (3) Becoming African Psychologists. Academics in higher education institutions have an ontoepistemological responsibility to encourage students to be critical of the hegemony of Western imperialist forms of knowledge. Therefore, decolonisation initiatives should include students becoming agentic actors who chart the course of their learning processes. Critical thinking skills may facilitate the formation of identities that increase students’ agency and creativity within traditionally rigid and hierarchical academic structures.